Keterlibatan Perempuan secara Formal dalam Pengelolaan Kegiatan Pariwisata di Desa Wisata Kebonagung, Bantul - Pratiwi, Diantika Ayu (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2022)
The tourism industry is seeing rapid growth. Nevertheless, the involvement of women in the official administration of the tourism industry remains limited. The objective of this study was to examine the extent of women's formal involvement in the management of tourist operations in Kebonagung tourist Village, located in Imogiri, Bantul Regency, in the Daerah Istimewa Yogyakarta Province. The analysis was conducted using the MOA (Motivation, Opportunity, and Ability) participation model. This study employed a qualitative methodology, utilizing techniques such as observation, interviews, and documentation. Data collection spanned a duration of 20 days, commencing on April 1st and concluding on April 20th, 2022. The researcher conducted interviews with three managers and pioneers of the Kebonagung Tourism Village,three female members who hold formal positions in the administration structure of the village, and three female local residents who actively participate in tourism activities. The findings of this study indicate that the level of women's engagement in formal management, as measured by factors such as motivation, opportunity, and ability, was significantly low. Additionally, the participation of women in formal management positions was shown to be extremely limited. The low participation of women in formal management in Kebonagung Tourism Village can be attributed to various factors. These include a lack of motivation among women to engage in management roles, limited opportunities that are not effectively utilized, inadequate or insufficient capabilities, as well as internal and external barriers that hinder women from formally participating in managing tourism activities.